Criticism in Theognidea - Porubjak, Matúš (Folia Philosophica, 2018)
This article focuses on the criticism in Theognidea. The most visible form of criticism is rooted in the social and political domain and is discussed in the first part of the article. The following part analyses more subtle and sophisticated forms of criticism by identifying Theognis’ use of irony and the peculiar message covered by his metaphors. The article concludes that the new poetical discourse of Theognidea contains a hidden but exact political message meant for a specific social community. This message was to be carefully considered, understood, and carried out. In this respect, Theognis is a philosophising poet using a high level of criticism and demanding the same from his audience.